Ayurveda Innovation for Global Health: A Scientific Review - Dwivedi, Anita; Kumar, Jitendra; Varsakiya, Nathabhai; Kathad, Divya Rani (International Research Journal of Ayurveda & Yoga, 2025)
Today’s global health is defined by the pursuit of preventative, holistic, and sustainable health practices to counteract the growing prevalence of lifestyle-related illnesses, mental health issues, and chronic diseases. One of the oldest medical systems in the world, Ayurveda originated in India and is becoming more and more well-known for its all-encompassing approach. Ayurveda, thus, is the “knowledge of life.” based on the notion of mental, physical, and spiritual equilibrium. Ayurveda uses lifestyle habits, individualized treatment, and natural therapies to promote well-being. In order to raise awareness of Ayurvedic principles, medicinal herbs, and holistic lifestyle practices, the Indian government has been celebrating Ayurveda Day on Dhanteras (Dhanawantari Jayanti) every year since 2016. The Government of India has been observing Ayurveda Day annually on Dhanteras (Dhanawantari Jayanti) to promote awareness of Ayurvedic principles, medicinal herbs, and holistic lifestyle practices. In Indian tradition, the knowledge of Ayurveda is believed to have been gifted to Lord Dhanvantari, the divine physician, by Lord Brahma. Ayurveda Day celebrates Lord Dhanvantari’s contributions and seeks to raise awareness about the fundamental principles of Ayurveda, its healing methods, and the lifestyle approaches it advocates for overall health and well-being. As the Ministry of Ayush prepares to celebrate the 9th Ayurveda Day on October 29, 2024, this year’s observance is set to be the most expansive yet, with over 150 countries joining in the celebrations under the theme “Ayurveda Innovations for Global Health.” Conclusions: This scientific review examines recent innovations in Ayurvedic practices, highlighting their contributions to global health, particularly in the context of modern scientific advancements and the growing demand for natural, sustainable healthcare solutions.